Intolerance of uncertainty in seriously injured veterans: a comparative analysis - Hromova, Hanna Mykhailivna (Insight: the psychological dimensions of society, 2020)
Intolerance of uncertainty is seen as tendency to perceiveunexpected and new circumstances as dangerous,and respond to them as a threat. It is known thatthe rejection of uncertainty is a factor that complicatesthe course and treatment of affective disorders(anxiety, depression, PTSD, sociophobia, etc.). The purpose of the research is to identify the relationshipbetween intolerance of uncertainty and signsof PTSD in veterans with serious injuries or disabilities.Methods: using the parametric Student’st-criterion and the non-parametric Mann-Whitneyand Kruskal-Wallis test, a comparative analysis wasperformed, and the Spearman coefficient ρ wasused to analyze the correlations. Data collected intwo groups of servicemen were compared. Officers(n = 47) and veterans who participated in the qualifyinground of the Invictus Games (n = 32) completedthe Intolerance of Uncertainty Scale questionnaire,the N. Carleton’s short version, and the PCL-5 PTSDSymptom Questionnaire. Results: it was found that groups of servicemen do not differ in the generallevel of intolerance of uncertainty, but there wasa significant difference on the scale of “depressinganxiety”. Subgroups with a higher level of intoleranceof uncertainty have significantly more manifestationsof post-traumatic stress symptoms. Intoleranceof uncertainty correlates with all clustersof PTSD symptoms in the general military group,and the “Inhibitory anxiety” subscale has a strongercorrelation with all clusters than the “Perspectiveanxiety” subscale. Conclusions: for the first time,the connection between IU and signs of PTSD inservicemen was studied in the Ukrainian sample.Veterans with serious injuries and disabilities havehigher scores on the “Inhibitory anxiety” subscale.The specificity of the connection between intoleranceof uncertainty in veterans with serious injuriesor disabilities, and signs of PTSD, is the lack of correlationwith aggressive and self-destructive behaviour(symptoms of cluster E). This feature reflects the specificsof the experience and manifestations of aggressionin veteran athletes with disabilities.